Combating Speculative Investment through Legal and Syariah Literacy: A Community Engagement Approach for Biased Young Investors - Aisa Rurkinantia; Bagas Heradhyaksa; Riza Fibriani; Ery Agus Priyono; Muhamad Azhar; Zulkarnaen Ahmad (Jurnal Pengabdian Hukum Indonesia (Indonesian Journal of Legal Community Engagement) JPHI, 2026)
Young investors under 30 now constitute 55.8% of Indonesia's 13.7 million individual investors. The national financial literacy index stands at 66.64% and the sharia financial literacy index at 43.42%. This gap leaves young investors highly vulnerable to Fear of Missing Out (FOMO). FOMO-based behaviour may violate Article 91 of Law Number 8 of 1995 on Capital Markets and contradicts DSN-MUI Fatwa Number 80/2011 on sharia investment principles. This program aimed to recalibrate the mindset of the Semarang Young Investor Community from speculative toward legally-aware, analytically-grounded investment practice. The study employed Participatory Action Research (PAR) through an in-person seminar on 1 November 2025 in Semarang. A five-pillar ecosystem was established: UIN Walisongo, IDX Central Java, Mirae Asset Sekuritas, AISA, and the Semarang Young Investor Community. Impact was measured through a mixed-methods design combining pre-test (n=65), post-test (n=45), and Focus Group Discussion (FGD). The mean comprehension score rose from 58.0 to 78.0 — a 20-point gain. The proportion in the High category increased from 19% to 65%. FGD findings confirm that participants identified influencer-based stock promotion as a potential violation of Article 91 and understood DSN-MUI Fatwa Number 80/2011 The program's novelty is threefold: targeting already-included, bias-vulnerable investors; integrating legal literacy as a core component; and combining PAR with a replicable five-pillar ecosystem model. This study proposes a paradigm shift from Education for Inclusion toward Education for Rationality and Legal Awareness. Investor vulnerability to FOMO constitutes a legal protection failure that legal literacy-based community engagement can directly address. This aligns the program with SDG 16 (Peace, Justice, and Strong Institutions), through its emphasis on investor legal protection, and SDG 4 (Quality Education), through its capacity-building outcome in the partner community.